Peran UMKM Sektor Pangan Dalam Meningkatkan Perekonomian Masyarakat Menengah Kebawah Kelurahan Kranji Bekasi Barat - Lutfiah Raihana Putri; Martini Martini; Achmad Nur Hidayaht (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
The role of UMKM in helping the community's economy as food sector entrepreneurs has contributed income to their families to meet the needs of the family such as basic needs, education, further sales capital, and others. This study aims to determine the role of food sector UMKM in improving the economy of the lower middle class in Kranji Village and helping the family economy and to find out the reasons why the people of Kranji Village choose food sector UMKM. The method used in this research is the Qualitative-Descriptive method. This research data collection uses observation, interviews, and documentation. the results of the study found that: 1) The role of food sector UMKM in improving the economy of culinary families such as being able to meet daily needs, meet children's school fees. And sales capital for the next. 2) The reasons for the Kranji Village Community to choose UMKM are due to basic human needs, relatively small capital, wide product variety, relatively easy marketing, flexibility of time and opportunities for work.